Modelling of a VSC-based multi-terminal HVDC network for dynamic stability analysis. Issue 1 (3rd January 2017) - Shinoda, Kosei; Guillaud, Xavier; Bacha, Seddik; Benchaib, Abdelkrim; Francois, Bruno
Abstract : Purpose: Self-commuted voltage source converter (VSC) can significantly extend the flexibility and operability of an HVDC system and be used to implement the concept of multi-terminal HVDC (MTDC) grid. To take full advantage of MTDC systems, its overall behaviour must be characterized in quasi static and dynamic states. Based on the numerous literatures, a dedicated two-level VSC model and its local controllers and DC grid voltage regulators are developed for this purpose. Furthermore, the requirement of the system to guarantee all the physical constrains must be well assessed and concrete demonstrations must be provided by numerical simulations. Design/methodology/approach: First, a two-level VSC model and its local controllers and DC grid voltage regulators are developed. Then, DC cable models are investigated and their characteristics are assessed in the frequency domain. Those developed models are combined to form a three-terminal HVDC grid system on Matlab/Simulink platform. To analyze the stability of this electrical system, the dynamics of the system against variations of power dispatch are observed. Findings: To analyze the stability of this electrical system, the dynamics of the system against variations of power dispatch are observed. The differences in the DC grid voltage dynamics and the power flow of the converter stations coming from the embedded primary controls are analysed, and the technical requirements for both cases are assessed. Originality/value: In this paper, the dynamic stability of an MTDC system has been analysed and assessed through an adequate simulation model, including its control scheme and the cable models. The interest of the improved PI model for cables is highlighted.